2016
DOI: 10.1016/j.jbtep.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory specificity in response to verbal and pictorial cues in clinical depression

Abstract: Background:  Depressed individuals have been consistently shown to exhibit problems in accessing specific memories of events from their past and instead tend to retrieve categorical summaries of events. The majority of studies examining autobiographical memory changes associated with psychopathology have tended to use word cues, but only one study to date has used images (with PTSD patients).  Objective: to determine if using images to cue autobiographical memories would reduce the memory specificity deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…Further, the lack of correlation with MDD and PTSD symptomatology suggests that the impaired executive control mechanism operates independently of the two disorders, and is instead a direct mechanism contributing to the phenomenon of reduced autobiographical memory specificity observed in these disorders. This is consistent with previous research on the relationship between executive control and OGM (Ellis & Ashbrook, 1988;Hertel & Hardin, 1990;Neshat-Doost et al, 2008;Ridout et al, 2016;Sumner et al, 2011).…”
Section: Capture and Rumination (Car)supporting
confidence: 92%
See 2 more Smart Citations
“…Further, the lack of correlation with MDD and PTSD symptomatology suggests that the impaired executive control mechanism operates independently of the two disorders, and is instead a direct mechanism contributing to the phenomenon of reduced autobiographical memory specificity observed in these disorders. This is consistent with previous research on the relationship between executive control and OGM (Ellis & Ashbrook, 1988;Hertel & Hardin, 1990;Neshat-Doost et al, 2008;Ridout et al, 2016;Sumner et al, 2011).…”
Section: Capture and Rumination (Car)supporting
confidence: 92%
“…Consistent with this expectation are findings that point to slower retrieval of positive memories in those with MDD (Ridout, Dritschel, Matthews, & O'Carroll, 2016).…”
Section: Conway and Pleydell-pearce's Self-memory Model According Tomentioning
confidence: 56%
See 1 more Smart Citation
“…Other recent studies, however, show that cue method has little effect. For example, no differences in memory specificity were observed in depressed individuals when using pictorial or verbal cues (Ridout, Dritschel, Matthews, & O'Carroll, 2016). Another study recently found that the interaction between self-relevance, valence, and depression scores accounted for differential performance between dysphoric and non-dysphoric participants on the AMT (Matsumoto & Mochizuki, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Positive autobiographical memories are associated with greater well-being, in contrast to the high anxiety that is related to negative memories ( Merrill et al, 2016 ). Several studies have revealed that, when presented with a cue that elicits a memory, depressed persons recall less specific, more general memories than do nondepressed individuals, whether the cues are words ( Champagne et al, 2016 ) or images ( Ridout et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%